2005
DOI: 10.1016/j.surfcoat.2004.07.083
|View full text |Cite
|
Sign up to set email alerts
|

Residual stress analysis—an important consideration for coating of stereolithography polymers

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…They concluded that smaller layer thickness and greater draft angle results in lower ejection force and increased life of the inserts. X-ray diffraction and hole drilling methods were used to analyse the residual stresses of metal coating and SL 5195 (Luan et al, 2005). The literature survey reveals that there are a number of works focusing on surface finish, accuracy, curl distortion and limited works concentrate on mechanical properties.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They concluded that smaller layer thickness and greater draft angle results in lower ejection force and increased life of the inserts. X-ray diffraction and hole drilling methods were used to analyse the residual stresses of metal coating and SL 5195 (Luan et al, 2005). The literature survey reveals that there are a number of works focusing on surface finish, accuracy, curl distortion and limited works concentrate on mechanical properties.…”
Section: Review Of Literaturementioning
confidence: 99%
“…24 For example, the nontoxic sodium hypophosphite (NaH 2 PO 2 $H 2 O) is usually used as a reductant to reduce the metal ions (e.g., Cu 2+ , Ni 2+ , Co 2+ and etc. Although this technology has been widely used for the production with uniform, less porous, adherent metal lm in many industrial applications (e.g., printed circuit board industry, [28][29][30] aerospace and automotive industry 31 ), there is no report on the preparation of Fe/Cu bimetallic particles for environmental application by using the electroless plating. [25][26][27] If the Fe/Cu bimetallic particles were prepared by using the electroless plating, the Fe 0 substrates would not be corroded to release plenty of Fe 2+ /Fe 3+ ions, which would facilitate the deposition of Cu on the Fe 0 substrates and enhance the bonding force between Cu and Fe 0 substrates.…”
Section: Introductionmentioning
confidence: 99%
“…However, their functionality can be enhanced by applying a layer of copper or nickel or their corresponding alloys [82,83].…”
Section: Processesmentioning
confidence: 99%